Reason and Impact Fire Forest and Land in Pekauman Sub-District, South Banjarmasin - Ayu Apriliani, Dara; Kumalawati, Rosalina (Jurnal Multidisiplin Indonesia, 2025)
Forest and land fires constitute a critical environmental challenge that extends beyond fire origin areas to affect urban residential communities. Pekauman Village exemplifies regions experiencing significant consequences from such fires, particularly manifested through deteriorating air quality and community well-being disruptions. This study aims to systematically describe community perceptions regarding the causal factors, multidimensional impacts, and adaptive strategies employed to address forest and land fire incidents in Pekauman Village, while evaluating the effectiveness of existing community responses. The research employed a qualitative descriptive approach utilizing triangulated data collection methods including structured observations, in-depth interviews with community members, and comprehensive documentation analysis to capture nuanced community perspectives and experiences. Findings reveal that community members predominantly attribute fire occurrences to anthropogenic activities as the primary causal factor. The most pronounced impacts identified include minor respiratory health complications and substantially reduced comfort levels in daily activities due to persistent haze conditions. Interestingly, despite widespread environmental degradation, economic impacts remain minimally perceived by residents, suggesting differential vulnerability across impact dimensions. Nevertheless, fires demonstrably compromise overall quality of life through cumulative environmental and health stressors. The study concludes that human-induced factors dominate fire causation in community perception, with health and comfort dimensions representing primary concern areas. The limited economic impact perception indicates potential gaps in long-term consequence awareness or differential socioeconomic resilience mechanisms within the community. This research effectively captures grassroots perspectives on fire management challenges, providing empirical foundation for developing community-centered mitigation strategies and policy interventions that address both immediate health concerns and broader environmental sustainability in fire-prone regions.